5-Formylcytosine organizes nucleosomes and forms Schiff base interactions with histones in mouse embryonic stem cells. Issue 12 (December 2018) - Raiber, Eun-Ang; Portella, Guillem; Martínez Cuesta, Sergio; Hardisty, Robyn; Murat, Pierre; Li, Zhe; Iurlaro, Mario; Dean, Wendy; Spindel, Julia; Beraldi, Dario; Liu, Zheng; Dawson, Mark; et al.
Abstract Nucleosomes are the basic unit of chromatin that help the packaging of genetic material while controlling access to the genetic information. The underlying DNA sequence, together with transcription-associated proteins and chromatin remodelling complexes, are important factors that influence the organization of nucleosomes. Here, we show that the naturally occurring DNA modification, 5-formylcytosine (5fC) is linked to tissue-specific nucleosome organization. Our study reveals that 5fC is associated with increased nucleosome occupancy in vitro and in vivo. We demonstrate that 5fC-associated nucleosomes at enhancers in the mammalian hindbrain and heart are linked to elevated gene expression. Our study also reveals the formation of a reversible-covalent Schiff base linkage between lysines of histone proteins and 5fC within nucleosomes in a cellular environment. We define their specific genomic loci in mouse embryonic stem cells and look into the biological consequences of these DNA–histone Schiff base sites. Collectively, our findings show that 5fC is a determinant of nucleosome organization and plays a role in establishing distinct regulatory regions that control transcription. A series of in vitro and in vivo studies has now shown that 5fC is linked to increased nucleosome occupancy and stability. Moreover, there is evidence that Schiff base formation between histones and 5fC impacts RNA polymerase II transcription activity in mouse embryonic stem cells.